Factors Affecting the Financial Structure Of Trading Firms In Samarinda - Rusmilawati, Rusmilawati (The International Journal of Accounting and Business Society, 2006)
One of the expenditure problems faced by the trading firms is the one related to the financial balance. The financial balance of a company could be achieved if the company did not have to face financial obstacles as a result of the umbalance between the available capital and the required capital. This research was aimed at investigating the simultaneously significant ejects of the factors of asset structure, sales growth rate profitability and operating leverage on the financial structure of the trading ï¬rms in Samarinaiafor short-term and long-term sources atultor self financial sources. lt was also intended to find out which of the tlontinant factors of asset structure. sales growth rate, profitability and operating leverage had the most signiï¬cant effect on the financial structure of the trading ï¬rms of Santarina'a for a short-term, a long-term and self-ï¬nancial sources (Networth). The research result indicated that simultaneously the factors used in this research had a signiï¬cant eï¬‚ect on both the short-term financial sources and self-ï¬nancial sources. The most dominant ï¬ictor which hatl the most significant eï¬‚fect on the short-term, long-term and self-ï¬nancial sources was the factor of proï¬tability. In the financial policy making process of the trading firms in Saniarinda, there was tendency towards the packing order lrehavior. By taking into consideration the profit factor, the companies would try to cover their financial problem with their self-financial sources, particularly with their proï¬t and their retained earnings. When their self capital source could not cover all their financial need, they would then consider their asset Â